Electronically Coupled Uranium and Iron Oxide Heterojunctions as Efficient Water Oxidation Catalysts. (3rd October 2019) - Leduc, Jennifer; Gönüllü, Yakup; Ruoko, Tero‐Petri; Fischer, Thomas; Mayrhofer, Leonhard; Tkachenko, Nikolai V.; Dong, Chung‐Li; Held, Alexander; Moseler, Michael; Mathur, Sanjay
Abstract: The most critical challenge faced in realizing a high efficiency photoelectrochemical water splitting process is the lack of suitable photoanodes enabling the transfer of four electrons involved in the complex oxygen evolution reaction (OER). Uranium oxides are efficient catalysts due to their wide range optical absorption ( E g ≈ 1.8–3.2 eV), high photoconductivity, and multiple valence switching among uranium centers that improves the charge propagation kinetics. Herein, thin films of depleted uranium oxide (U3 O8 ) are demonstrated grown via chemical vapor deposition effectively accelerate the OER in conjunction with hematite (α‐Fe2 O3 ) overlayers through a built‐in potential at the interface. Density functional theory simulations demonstrate that the multivalence of U and Fe ions induce the adjustment of the band alignment subject to the concentration of interfacial Fe ions. In general, the equilibrium state depicts a type II band edge as the favored alignment, which improves charge‐transfer processes as observed in transient and X‐ray absorption (TAS and XAS) spectroscopy. The enhanced water splitting photocurrent density of the heterostructures ( J = 2.42 mA cm −2 ) demonstrates the unexplored potential of uranium oxide in artificial photosynthesis. Abstract : The oxygen evolution reaction is accelerated by thin films of depleted U3 O8 grown via chemical vapor deposition in conjunction with α‐Fe2 O3 overlayers through a built‐in potential at the interface. This buried junction nearly doubles the photocurrent density compared to monolithic hematite photoanodes and opens up new perspectives for turning depleted nuclear fuels into efficient catalysts for solar energy conversion.